Multifaceted neuroprotective approach of Trolox in Alzheimer's disease mouse model: targeting Aβ pathology, neuroinflammation, oxidative stress, and synaptic dysfunction - Tahir, Muhammad; Kang, Min Hwa; Park, Tae Ju; Ali, Jawad; Choe, Kyonghwan; Park, Jun Sung; Kim, Myeong Ok (Frontiers in Cellular Neuroscience, 2024)
Alzheimer's disease (AD) is a progressive neurodegenerative disorder pathologically characterized by the deposition of amyloid beta (Aβ) plaques and neurofibrillary tangles (NFTs) in the brain. The accumulation of these aggregated proteins causes memory and synaptic dysfunction, neuroinflammation and oxidative stress. Current research study aimed to assess neuroprotective properties of vitamin E (VE) analog trolox in Aβ1-42-induced AD mouse model. Aβ1-42 5μL/5min/mouse) was injected intracerebroventricularly (i.c.v) into wild-type adult mice brain to induce AD-like neurotoxicity. For biochemical analysis, western blotting and confocal microscopy were performed. Remarkably, intraperitoneal (i.p) treatment of trolox (30 mg/kg/mouse for 2 weeks) reduced the AD pathology by reducing the expression of Aβ, phosphorylated tau (p-tau), and beta-site amyloid precursor protein cleaving enzyme1 (BACE1) in both cortex and hippocampus regions of mice brain. Furthermore, trolox-treatment decreased neuroinflammation by inhibiting Toll-like receptor 4 (TLR4), phosphorylated nuclear factor-κB (pNF-κB) and interleukin-1beta (IL-1β) and other inflammatory biomarkers of glial cells (Ionized calcium-binding adaptor molecule 1 (Iba1) and Glial fibrillary acidic protein (GFAP)). Moreover, trolox reduced oxidative stress by enhancing the expression of nuclear factor erythroid-related factor 2 (NRF2) and heme oxygenase 1 (HO1). Likewise, trolox-induced synaptic markers including synaptosomal associated protein 23 (SNAP23), synaptophysin (SYN), and post-synaptic density protein 95 (PSD-95), and memory functions in AD mice. Our findings could prove to be a useful and novel strategy for the investigation of new medications to treat AD-associated neurodegenerative diseases.